Coryanthes macrantha (Orchidaceae: Stanhopeinae) and their floral and extrafloral secretory structures: an anatomical and phytochemical approach. Issue 5 (2nd September 2022) - Casique, Jorgeane Valéria; Soares, Marcos Vinícius Batista; da Silva, Edilson Freitas; Kikuchi, Tatiani Yuriko; Andrade, Eloisa Helena de Aguiar; Mastroberti, Alexandra Antunes
Abstract: Coryanthes is one of the most fascinating genera of Stanhopeinae (Orchidaceae) because of its complex pollination mechanism and the peculiar structures of its flowers. Although Coryanthes macrantha is widely studied, investigation of the secretory structures and floral biology is important to understand the mechanisms and ecology of pollination, which deserve attention despite the difficulties of collecting fertile material in nature. We conducted a morpho-anatomical analysis of the floral and extrafloral secretory structures of C. macrantha to better understand the secretory structures, contribute to the knowledge of its floral biology and/or pollination processes and understand the ecological function of these structures. The analysis revealed that C. macrantha has epidermal osmophores with unicellular papillae that were foraged by male Eulaema bees, floral nectaries in the sepals and extrafloral nectaries in the bracts. In both the floral and extrafloral nectaries, the nectar is exuded by the stomata. Azteca ants foraged the bract and sepal nectaries in pre-anthesis and post-anthesis. We also described the secretory epidermis of pleuridia, and the mode of secretion of osmophores and nectaries and found that they attract specific foraging agents. Abstract : This study brings unprecedented analyses of Coryanthes macrantha, a fascinating species of Orchidaceae, with wide occurrence in the Brazilian Amazon. This species present an ingenious pollination mechanism, due to the peculiar structure of the labellum. Osmophores, structures that secrete volatile substances, are located in the labellum and are responsible for attracting male Euglossini bees. The attracted bees fall into a structure like a bucket (epichile) full of a liquid, and later exit through a small lateral passage, thus removing the pollinarium. In C. macrantha, ants, nectaries, trichomes, osmophores, bees and stomata were observed and relationships between them were investigated.